Lipocalin 2 prevents oral cancer metastasis through carbonic anhydrase IX inhibition and is associated with favourable prognosis. (27th April 2016) - Lin, Chiao-Wen; Yang, Wei-En; Lee, Wei-Jiunn; Hua, Kuo-Tai; Hsieh, Feng-Koo; Hsiao, Michael; Chen, Chia-Cheng; Chow, Jyh-Ming; Chen, Mu-Kuan; Yang, Shun-Fa; Chien, Ming-Hsien
Summary: Our study elucidated the clinical and prognostic significance of LCN2 in OSCC among the Taiwanese population. Moreover, we observed that LCN2 suppresses cell motility by downregulating CAIX protein level via HIF-1α-mediated transcriptional regulation and miR-4505-mediated post-transcriptional regulation. Abstract : Lipocalin 2 (LCN2), a secreted glycoprotein, is up- or downregulated in different human cancers. At present, the functional role of LCN2 in the progression of oral squamous cell carcinoma (OSCC), which accounts for most head and neck cancers, remains poorly understood, particularly with respect to its involvement in invasion and metastasis. In this study, we observed that LCN2 expression decreased in patients with OSCC and lymph node metastasis compared with that in patients without metastasis. A higher LCN2 expression correlated with the survival of patients with OSCC. Furthermore, LCN2 overexpression in OSCC cells reduced in vitro migration and invasion and in vivo metastasis, whereas its silencing induced an increase in cell motility. Mechanistically, LCN2 inhibited the cell motility of OSCC cells through hypoxia-inducible factor (HIF)-1α-dependent transcriptional inhibition of the carbonic anhydrase IX (CAIX). CAIX overexpression relieved the migration inhibition imposed by LCN2 overexpression in OSCC cells. Moreover, a microRNA (miR) analysis revealed that LCN2 can suppress CAIX expression and cell migration through miR-4505 induction. Examination of tumour tissues from patients with OSCC and OSCC-transplanted mice revealed an inverse correlation between LCN2 and CAIX expression. Furthermore, patients with LCN2 strong /CAIX weak revealed the lowest frequency of lymph node metastasis and the longest survival. Our findings suggest that LCN2 suppresses tumour metastasis by targeting the transcriptional and post-transcriptional regulation of CAIX in OSCC cells. LCN2 overexpression may be a novel OSCC treatment strategy and a useful biomarker for predicting OSCC progression.